Integrasi Etika Dalam Kebijakan Kurikulum Merdeka Sebagai Upaya Peningkatan Mutu Pendidikan - Bayu Anggoro Putro, Bayu Anggoro; Anggraini , Lussy; Nadya Fathni , Luthfia; Anjarsari, Resi; Resa, Ibna (Program Studi Pendidikan Agama Islam, 2025)
The purpose of this study is to examine one of the important foundations of the independent curriculum, namely how ethics are integrated into the independent curriculum policy and to find out the supporting and inhibiting factors along with problem solutions. The method used is a qualitative approach and the type of research emphasized is literature study. Through the post-positivism paradigm which provides data interpretation based on facts sourced from scientific journals and books associated with ethical theory. The results and discussion show that the integration of ethics is urgent to be applied to independent curriculum learning at elementary, secondary, and higher education levels by looking at the characteristics of each student. Findings of internal supporting factors were obtained, namely (a) Support from leaders; (b) Commitment of students, students, teachers, and lecturers; (c) Positive orientation of education policy makers. External supporting factors include: (a) Collaboration between parents and the community; and (b) Development of the times. In addition, internal inhibiting factors were found: (a) Limited facilities and infrastructure; and (b) Lack of teacher and lecturer training, while the external factors were: (a) Existence of SARA conflicts; and (b) The influence of media and technology.